INTRODUCING AUTOMATION EDUCATIONAL COMPLEX IN THE EDUCATIONAL PROCESS OF HIGH SCHOOL - Kateryna P. Osadcha; Viacheslav V. Osadchyi (Открытое образование (Москва))
The article presents the results of the pedagogical experiment to introduce a series of automated teaching methods in the educational process at Melitopol State Pedagogical University named after Bogdan Khmelnitsky, conducted in 2012–2014. Developed and tested systems in the disciplines “Operating Systems”, “Basic scientifi c research”, “Technologies for Information Management”, “Software Testing” consist of an electronic textbook, course and distance learning unit “Electronic Journal”. Analysis of the results of the pedagogical experiment showed that the use of automated teaching methods in the educational process of the university positively affects the improvement of student performance.